Associations Between the Apolipoprotein E ε4 Allele and Reduced Serum Levels of High Density Lipoprotein a Cognitively Normal Aging Han Chinese Population - Li, Wei; Li, Yong; Qiu, Qi; Sun, Lin; Yue, Ling; Li, Xia; Xiao, Shifu (Frontiers in Endocrinology, 2019)
Abstract Background: Previous studies have confirmed that APOE genotype is associated with lipid metabolism, but related studies are inconsistent. Therefore, we conducted this cross-sectional study to explore the associations between apolipoprotein E (APOE) genotypes and serum levels of fasting blood sugar, triglycerides, total cholesterol, high density lipoprotein and low density lipoprotein in a cognitively normal aging Han Chinese population. Methods: 169 community elders with normal cognitive function were included in the study. Based on multiplex amplification refractory mutation system polymerase chain reaction (PCR), these subjects were divided into three groups: 1) E2/2 or E2/3 (APOE E2); 2) E3/3 (APOE E3); and 3) E2/4, E3/4, or E4/4 (APOE E4). Correlations of serum levels of fasting blood sugar, triglycerides, total cholesterol, high density lipoprotein and low density lipoprotein with APOE genotypes were assessed. Results: The results of single factor ANOVA Least—Significant Difference (LSD) analysis showed that the concentration of high density lipoprotein (HDL) in APOE E2 and E3 groups was higher than that in E4 groups (p<0.05). Logistic regression analysis also suggested that a lower level of high density lipoprotein was associated with the E4 allele (adjusted odds ratio 0.162, 95% confidence interval 0.031~ 0.840, P=0.030). Conclusion: A lower serum level of high density lipoprotein was significantly correlated with APOE E4 status in a cognitively normal aging Han Chinese population. Keywords: APOE E4, cognitively normal aging, high density lipoprotein, Chinese